Multidisciplinary Management of Children with Occult Spinal Dysraphism: A Comprehensive Journey from Birth to Adulthood - Ignazio G. Vetrano; Arianna Barbotti; Alessandra Erbetta; Sabrina Mariani; Stefania M. Bova; Luca Colombo; Valentina Caretti; Federica Marinoni; Elettra Vestri; Giorgio G. O. Selvaggio; Laura G. Valentini (MDPI AG, 2022)
Occult spinal dysraphism (OSD) comprises different forms of failure in embryogenic development that can lead to genitourinary, spinal, or lower limb alterations, thus determining progressive neurological deterioration. The correct management of children harboring OSD represents a significant issue during their life up to adulthood. However, patients often have to entertain individual consultations with each specialist. We settled on a multidisciplinary team comprising pediatric neurosurgeons, urologists, neurologists, orthopedists, and other supporting physicians. We present the results of such actions by analyzing a series of 141 children with OSD subjected to neurosurgical procedures, evaluating the impact of multidisciplinary management on outcomes. We also evaluated the specific actions according to the different ages of OSD patients from birth to adulthood to provide a schematic plan that could represent a basis for establishing and disseminating the need for a multidisciplinary approach in OSD management. The multidisciplinary team allows all consultants to see the patient together, covering specific aspects of history and examination pertinent to their management. Offering a one-stop service prevents coordination issues between the different medical teams, avoids delays or cancellations of the various appointments, optimizes cost-effectiveness, and improves efficiency and parents' satisfaction.